Peculiarities of rape plant identification features manifestation and their use during formation of national variety sources - Н. В. Лещук; М. М. Таганцова; С. Л. Мельничук (Plant Varieties Studying and Protection)
Scientific approaches to formation of national variety sources of spring and winter barley by State Registration of new varieties and their right protection.